Infección de vías urinarias como causa de amenaza de parto pretérmino en el Hospital Nicolas Cotto Infante de Vinces, Los Ríos, enero – junio 2019. - Aguirre Vasquez, Zacarias Sebastian (2020)
The UTI is one of the most frequent complications during pregnancy, it is one of the causes and the most predominant in high rate of threat of preterm birth and with it all the immersed complications both maternal and fetal, the objective of the present study is to determine if the IVU is the cause of APP at the Nicolas Cotto Infante Hospital in the city of Vinces. Methods: Retrospective, descriptive type research, which is subject to a universe of 450 patients and a sample of 125 pregnant women with APP diagnosis at the Nicolás Cotto Infante de Vinces Hospital, in a period from January to June 2019, determines the patient age, maternal-fetal complications, gestational age, previous number of prenatal controls, most frequent UTI, risk factors added by means of a statistical analysis. Result: the present study found that the age of the patients between 13 and 20 years corresponds to 51%, the gestational age that mostly presents complications was between 31 to 36.6 giving a percentage of 66%, the most frequent clinical form was cystitis with 50%, prenatal controls were a minimum of 1 to 3 corresponding to 52%, and the most important risk factor fell on low socioeconomic level with 62%. Conclusions: the percentage of association between IVU and APP in patients treated in the Gynecology - Obstetrics department of Vinces HBNCI is significantly high.